Abundance and distribution of the swimming crab Callinectes danae Smith, 1869 (Crustacea, Decapoda, Portunidae) in the Ubatuba region, southeastern Brazil - Antunes, Mariana [UNESP]; Fransozo, Vivian [UNESP]; Bertini, Giovana [UNESP]; Teixeira, Gustavo Monteiro [UNESP]; Fransozo, Adilson [UNESP] (Taylor & Francis As, 2015)
This study analysed the spatio-temporal distribution of Callinectes danae considering some environmental factors in three bays in Ubatuba, SAo Paulo, Brazil: Ubatumirim, Ubatuba and Mar Virado. Sampling was performed monthly (from January 1998 to December 1999) using a shrimp fishery boat provided with double rig nets. Six transects were established in each bay, three being in areas protected from wave action (at 5, 7.5 and 10 m depth) and three in exposed areas (at 10, 15 and 20 m). A total of 3039 specimens were obtained. The distribution of C. danae differed between years, among seasons, bays and transects (K-W; p < 0.05). This species occurred with a higher abundance in the shallow transects of all bays studied. These transects were characterized by substrate composed of fine or very fine sand and by silt and clay, higher values of bottom temperature and lower salinity values. Based on canonical correspondence analysis, the most relevant environmental factors for the spatio-temporal distribution of C. danae, in addition to salinity, were the bottom-water temperature and the sediment texture.
Keywords: Brachyura; environmental factors; South Atlantic; temporal and spatial distribution